Mothers' instinct [videorecording (DVD)] - Conradt, Sarah; Chastain, Jessica, 1977-; Hathaway, Anne, 1982-; Nikitin, Anne; Charles, Josh, 1971-; Danielsen Lie, Anders, 1979-; O'Connell, Eamon Patrick; Bielitz, Baylen D.; Lagerfelt, Caroline; Abel, Barbara, 1969- (Decal, 2024)
Set in the early 1960s, best friends and neighbors Alice and Celine both live an idyllic traditional lifestyle, but life's perfect harmony is suddenly shattered after a tragic accident. Guilt, suspicion and paranoia unravel their sisterly bond and a psychological battle begins.